Challenges in neurological practice in developing countries - Sanjay Pandey (Wolters Kluwer Medknow Publications, 2012)
The burden of neurological illness is much higher in developing countries. Neurological disorders in these countries are mainly due to poverty and malnutrition. Spectrums of diseases are also different in comparison with developed countries. Lack of resources, ignorance, and overpopulation make it very difficult and challenging to tackle this problem. Majority of the patients are seen by general practitioners who have little knowledge about neurological illnesses. Most of the countries have very few or no neurologist. There is a greater need of taking neurological care at primary care level where majority of the patients struggle with epilepsy, stroke and neuroinfections.